2016
DOI: 10.1021/acs.jmedchem.5b01098
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Bacterial Division Protein FtsZ

Abstract: Similar to its eukaryotic counterpart, the prokaryotic cytoskeleton is essential for the structural and mechanical properties of bacterial cells. The essential protein FtsZ is a central player in the cytoskeletal family, forms a cytokinetic ring at mid-cell, and recruits the division machinery to orchestrate cell division. Cells depleted of or lacking functional FtsZ do not divide and grow into long filaments that eventually lyse. FtsZ has been studied extensively as a target for antibacterial development. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 234 publications
(607 reference statements)
2
70
0
1
Order By: Relevance
“…Because most of the reported FtsZ inhibitors do not have or only have weak inhibitory effect against the Gram-negative strains (Haranahalli et al, 2016; Hurley et al, 2016), we therefore initiated the screen with B. subtilis 168 in the presence of a small compound library including 40 natural products, 20 natural product derivatives and 140 general compounds which are either commercially available or synthesized in our laboratory. The screen (Stokes et al, 2005; Li et al, 2015) generated one potential hit, 2-((E)-4-hydroxystyryl)-1-methyl-4-((Z)-(3-methylbenzo[d]thiazol-2(3H)-ylidene)methyl)quinolin-1-ium iodide (compound 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because most of the reported FtsZ inhibitors do not have or only have weak inhibitory effect against the Gram-negative strains (Haranahalli et al, 2016; Hurley et al, 2016), we therefore initiated the screen with B. subtilis 168 in the presence of a small compound library including 40 natural products, 20 natural product derivatives and 140 general compounds which are either commercially available or synthesized in our laboratory. The screen (Stokes et al, 2005; Li et al, 2015) generated one potential hit, 2-((E)-4-hydroxystyryl)-1-methyl-4-((Z)-(3-methylbenzo[d]thiazol-2(3H)-ylidene)methyl)quinolin-1-ium iodide (compound 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a number of small molecule inhibitors of FtsZ have already been revealed to perturb FtsZ polymerization and inhibit bacterial cell division (Bierer et al, 1998; Beuria et al, 2005; Schaffner-Barbero et al, 2012; Li et al, 2015; Haranahalli et al, 2016; Hurley et al, 2016; Qiang et al, 2016; Bi et al, 2017). These studies suggest that the molecules impair bacterial growth through disrupting the dynamic assembly or/and GTP hydrolysis of FtsZ.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, Cdv3 and MinC may be only 2 representative genes that can be genetically manipulated in this fashion to disrupt divisome assembly and to promote cell elongation; other FtsZ-regulatory genes (28) may also be promising targets for this purpose. Furthermore, the addition of chemical inhibitors of FtsZ might be expected to have similar results (29), although they may not be practical for scaled applications.…”
Section: Discussionmentioning
confidence: 99%
“…Several characteristics render FtsZ a potential target for the development of new antibacterial agents: (i) it plays an essential role in bacterial cell division [45]; (ii) the structure and function of FtsZ are conserved across bacterial species [17,20]; (iii) it is absent in eukaryotes [69,70]; (iv) its structural and biological properties are well studied. So far, there are no drugs on the market targeting at FtsZ, but many researchers have made great efforts in studying FtsZ targeting compounds and their studies revealed that FtsZ inhibitors can lead to bacterial cell death via inhibition of cell division [71][72][73][74]. Most of these inhibitors will be discussed in the following sections.…”
Section: Ftsz Inhibitorsmentioning
confidence: 99%